MORAL KRISTIANI DAN KEPRIHATINAN SOSIAL - Aman, Peter C. (MELINTAS An International Journal of Philosophy and Religion (MIJPR), 2006)
Ever since the nineteenth century, the Church has redefined and repositioned her role concerning social conditions and problems of the secular world. Her concern and engagement are rooted in her very self-definition as the People of God and the Sacrament of Salvation. The definition calls for her involvement in the world so as to transformthe world into the anticipation of the Kingdom of God. The article traces the theological foundation of suchconviction, the authority of the church for such involvement, the normative teaching of Jesus himself and the primacy of solidarity.